2019
DOI: 10.3389/fendo.2019.00771
|View full text |Cite
|
Sign up to set email alerts
|

Association of GPx1 P198L and CAT C-262T Genetic Variations With Polycystic Ovary Syndrome in Chinese Women

Abstract: Background: Oxidative stress plays an important role in the pathogenesis of polycystic ovary syndrome (PCOS). Glutathione peroxidase 1 (GPx1) and catalase (CAT) are the major intracellular antioxidant enzymes that can detoxify hydrogen peroxide into water, preventing cellular injury from reactive oxygen species. The aim of the present study was to investigate the association of GPx1 P198L (Pro198Leu, C559T, rs1050450) and CAT C-262T (rs1001179) genetic polymorphisms with the risk of PCOS and evaluate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The catalase protects the genome of mouse oocytes from oxidative damage during meiotic maturation and its activity in ovarian granulosa and theca cells are known to increase during ovarian development and luteinization [22]. In addition, the cooperative effect of gpx and catalase has been investigated in other studies [45][46][47]. For instance, the upregulation of gpx supported catalase activity in the presence of hydrogen peroxide, thereby inhibiting ROS-induced cell death [46].…”
Section: Discussionmentioning
confidence: 99%
“…The catalase protects the genome of mouse oocytes from oxidative damage during meiotic maturation and its activity in ovarian granulosa and theca cells are known to increase during ovarian development and luteinization [22]. In addition, the cooperative effect of gpx and catalase has been investigated in other studies [45][46][47]. For instance, the upregulation of gpx supported catalase activity in the presence of hydrogen peroxide, thereby inhibiting ROS-induced cell death [46].…”
Section: Discussionmentioning
confidence: 99%
“…Serum estradiol (E 2 ), total testosterone (TT), luteinizing hormone (LH), follicle‐stimulating hormone (FSH), sex hormone‐binding globulin (SHBG), triglyceride (TG), total cholesterol (TC), HDL‐cholesterol (HDL‐C), LDL‐cholesterol (LDL‐C), apolipoprotein (apo)A1, apoB, total oxidant status (TOS), malondialdehyde (MDA) and total antioxidant capacity (T‐AOC) levels, plasma insulin and glucose concentrations, homeostatic model assessment of insulin resistance (HOMA‐IR), free androgen index (FAI) and oxidative stress index (OSI) were determined or assessed as described previously 4,22,26 …”
Section: Methodsmentioning
confidence: 99%
“…Oxidative stress plays an important role in the pathogenesis of PCOS, 4,6,22,23 and patients with PCOS have increased MPO levels 24 . However, it remains unknown whether the MPO G‐463A and CYBA C242T SNPs are related to PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with diabetes show mutations and alterations in genes involved in the antioxidant pathway that influence the progression of the disease 47 . Studies conducted among Chinese women with PCOS have reported an association between this syndrome and the P198L polymorphism of GPX1 48 . However, a study in Iran found no association between the risk of PCOS and GPX1 (rs1050450) or SOD2 (rs4880) polymorphisms 49 …”
Section: Metabolism and Pcosmentioning
confidence: 99%